2004
DOI: 10.1111/j.1398-9995.2004.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in pathogenesis and management of hypereosinophilic syndromes

Abstract: Idiopathic hypereosinophilic syndrome is a largely heterogeneous disorder defined until now as persistent marked hypereosinophilia of unknown origin generally complicated by end‐organ damage. Recent studies clearly indicate that many patients fulfilling the diagnostic criteria of this syndrome can now be classified as presenting one of two major disease variants: the myeloproliferative or the lymphocytic variant. Research in cellular and molecular biology has provided firm evidence for the existence of discret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
150
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 69 publications
(118 reference statements)
1
150
0
5
Order By: Relevance
“…2 Lymphocyte-variant hypereosinophilia relates to the existence of clonal, pathogenetic T-cell subsets with an aberrant surface immunophenotype (for example, CD3 À CD4 þ , CD4 þ CD7 À , CD3 þ CD4 À CD8 À ), which overproduce eosinophilopoietic cytokines such as interleukin-5 (IL-5) and other Th2 cytokines such as IL-4, IL-13 and granulocyte macrophage colonystimulating factor. 3,4 In these cases, the eosinophilia is nonclonal. In rare instances, transformation of the clonal T cells to T-cell lymphoma has been reported, although lymphocytevariant hypereosinophilia generally follows a benign course.…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…2 Lymphocyte-variant hypereosinophilia relates to the existence of clonal, pathogenetic T-cell subsets with an aberrant surface immunophenotype (for example, CD3 À CD4 þ , CD4 þ CD7 À , CD3 þ CD4 À CD8 À ), which overproduce eosinophilopoietic cytokines such as interleukin-5 (IL-5) and other Th2 cytokines such as IL-4, IL-13 and granulocyte macrophage colonystimulating factor. 3,4 In these cases, the eosinophilia is nonclonal. In rare instances, transformation of the clonal T cells to T-cell lymphoma has been reported, although lymphocytevariant hypereosinophilia generally follows a benign course.…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…Hypoproteinemia is a common finding in equine MEED cases (LA PERLE et al, 1998;GEHLEN et al, 2003;ROUFOSSE et al, 2004). According to HENSON et al (2002), it is detected in 58% of MEED cases, and reflects the protein-losing enteropathy seen in affected horses.…”
mentioning
confidence: 99%
“…Eosinophilia occurs in approximately 14% of MEED cases (BOSSELER et al, 2013;MAULDIN & PETERS-KENNEDY, 2016), and leukocytosis was also previously reported (GEHLEN et al, 2003;BOSSELER et al, 2013). Etiopathogenesis of MEED is unknown; various factors could be involved in the stimulation and chemotaxis of eosinophils that ultimately lead to multisystemic infiltrates (LA PERLE et al, 1998;ROUFOSSE et al, 2004;MAULDIN & PETERS-KENNEDY, 2016). Deregulated production of eosinophilopoietic cytokines (granulocyte-macrophage colonystimulating factor, interleukin-3, and interleukin 5 [IL-5]) is responsible for hypereosinophilic syndromes in humans (ROUFOSSE et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophilia may occur in a number of diseased conditions, which include parasitic infections, allergies, collagen vascular diseases, and neoplastic disorders. Another morbid condition distinct from these secondary eosinophilias, idiopathic hypereosinophilic syndrome (idiopathic HES), is a condition in which eosinophilia persists without any apparent etiology [7]. …”
mentioning
confidence: 99%